The evaluation of ignation pedadogical paradigm framework to engineering ethics education - Shahrir Abdullah,; Haryanti Mohd Affandi,; Victor, Gerald (Penerbit Universiti Kebangsaan Malaysia, 2022)
Teaching and learning in higher education has gone through a series of transformation in recent decades. Engineering education is one area that would be crucial to undergo such transformation due to the complex nature of engineering application in industries today. The problem facing engineering graduates is the ability to competently solve real world problems using the knowledge learnt during their tertiary education. The learning approach towards problem solving and critical thinking weren’t sufficiently developed throughout the curriculum. One of the theories of learning that was considered was coined by Piaget, cognitive constructivism theory which uses cognitive tools and in collaboration with the environment learners are exposed to. By incorporating such student-centered learning with group learning would improve the students’ achievement in the learning outcome and increase the learning efficacy. This paper describes the application of Ignation Pedagogical Paradigm (IPP) being applied as a model framework in the teaching of one of the courses offered in Bachelor of Mechanical Engineering, i.e. Professional Practice towards strengthening their competencies. By applying a structured formative assessment centered learning environment, the instructor would be able to provide a more holistic learning experience to the students using the cognitive constructivism theory of learning. The results show that the proposed IPP framework is able to complement affectively with the learning theories for engineering education achieving the course outcomes and students would be able to improve their competency in solving complex problem.